PENGARUH PEMAHAMAN SISTEM INFORMASI AKUNTANSI, E-COMMERCE, MODAL USAHA DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA: (Studi Pada Mahasiswa Akuntansi Di Solo Raya) - Andika Setyawan; Wikan Budi Utami; Suhesti Ningsih (Jurnal Ilmiah Akuntansi, 2024)
This research was conducted determine the influence of accounting information systems, e-commerce, business capital, motivation on entrepreneurial interest of accounting students in Solo Raya. This research uses primary data by collecting data through questionnaires. The sampling in the research was accidental sampling. The research sample consisted of 100 respondents with accounting students from 18 universities in Solo Raya. The data analysis method uses descriptive statistical tests, data quality test, classical assumption tests, t statistical tests, and coefficient of determination tests. The research results state that Accounting Information Systems, E-Commerce, Business Capitals, and Motivation influence Entrepreneurial Interest.